2009
DOI: 10.1590/s0103-90162009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic view of vegetation and carbon and nitrogen cycles in a cerrado ecosystem, southeastern Brazil

Abstract: Carbon and nitrogen biogeochemical cycles in savannas are strongly regulated by the seasonal distribution of precipitation and pulses of nutrients released during the wetting of the dry soil and are critical to the dynamics of microorganisms and vegetation. The objective of this study was to investigate the spatial and temporal variability of C and N isotope ratios as indicators of the cycling of these elements in a cerrado sensu stricto area, within a protected area in a State Park in the state of São Paulo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 33 publications
3
25
0
8
Order By: Relevance
“…Consistent with previous studies in several ecosystems with contrasting N availability, we found a large range of leaf d 15 N values in both cerradão and SDF sites (Michelsen et al 1996;Nadelhoffer et al 1996;Bustamante et al 2004;Ometto et al 2006;Coletta et al 2009). The N-poor cerradão site had a larger range of leaf d 15 N values in comparison to the SDF; however, this difference seems very small (1.6‰) to characterize a higher diversity of N use strategies in the N-poor cerradão site.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies in several ecosystems with contrasting N availability, we found a large range of leaf d 15 N values in both cerradão and SDF sites (Michelsen et al 1996;Nadelhoffer et al 1996;Bustamante et al 2004;Ometto et al 2006;Coletta et al 2009). The N-poor cerradão site had a larger range of leaf d 15 N values in comparison to the SDF; however, this difference seems very small (1.6‰) to characterize a higher diversity of N use strategies in the N-poor cerradão site.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, plants associated with mycorrhizal fungi tend to have lower d 15 N values than nonmycorrhizal plants, mainly because discrimination against 15 N occurs during fungal N assimilation (Högberg et al 1996;Hobbie et al 2000). Legume trees, which might obtain substantial amounts of their N inputs by association with N-fixing bacteria, tend to present higher leaf N concentration relative to nonlegumes (Vitousek et al 2002;Bustamante et al 2004;Bai et al 2009;Coletta et al 2009). In addition, legumes would presumably have d 15 N values between 0 and 2‰ (Högberg 1997), because there is no isotopic discrimination during biological fixation of atmospheric N2, which has a d 15 N of near 0‰ (see Dawson et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were filtered (0.45 lm) immediately and frozen from £ 6 h after collection until they were chemically and isotopically analyzed. Our sampling design does not allow us to capture seasonal or within-canopy variation in d 15 N. However, our main trends are much larger than observed seasonal changes in other systemstypically 1-2‰ at most (Ometto et al, 2006;Coletta et al, 2009;Bragazza et al, 2010) -and within-canopy variation reported elsewhere (Bergstrom & Tweedie, 1998) is negligible.…”
Section: New Phytologistmentioning
confidence: 71%
“…13 C measurements contribute to our understanding of plant ecophysiology, e.g., how plants respond to water stress or differences in light availability, as well as canopy-level CO 2 gradients and exchanges (Buchmann et al 1996, Buchmann et al 1997, Dawson et al 2002, Coletta et al 2009). At continental and global scales, d…”
Section: Introductionmentioning
confidence: 99%